SLANG OF TRANSVESTITE IN PASAR MINGGU “SOCIOLINGUISTIC APPROACH” - Suhardianto Suhardianto; Retno Setya Budiasningrum (IdeBahasa, 2022)
The purpose of this research is to analyze the process of formating of slang words in the transvestite community in Pasar Minggu. Slang is the use of informal words and expressions that they are not considered as standard language in daily conversation. The researcher collected the data used an interview method. The researcher interviewed the sample data taken from the transverstite found in Pasar Minggu. The researcher naturally asked the transvetite some daily words used and made a note. The data collected and analyzed to find ou the way how the transvestite constructed the words of slang. The data analyze used qualitative process method. The researcher analyzed each words taken from the sample data and descriptively constructed the words refers to the sociolinguistcs theory. From the twenty data sample taken from the transvestite the result shown that the use of slang language in transvestite community is increasingly widespread. The word used by transvestite community with having a regular and irregular pattern. Regular pattern with the suffix "ONG" sound, the vowel in the first syllable is replaced with the letter "E". Vowels in the second syllable replaced by "ONG", and there are also a few words were changed with suffix become "ES".